Electrode layer-forming curable organopolysiloxane composition, laminate provided with electrode layer, use thereof, and method for producing same
By using the electrode layer formative curable organopolysiloxane composition, the problem of degradation of the electrode layer viscoelasticity and conductivity in a high temperature environment is solved, and high performance of the electrode layer is maintained at a high temperature of 100°C or above, thereby improving the reliability of the actuator.
Patent Information
- Application Number
- CN202380063861.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-15
Smart Images

Figure BDA0005297777610000201 
Figure BDA0005297777610000202 
Figure BDA0005297777610000211
Abstract
Description
Technical Field
[0001] The present invention relates to a method for forming a conductive film having excellent conductivity and a temperature-dependent viscoelasticity through a curing reaction.
[0002] Electrode layer-forming curable organopolysiloxane composition having low dependence on electrode layer, and using the same
[0003] A laminate of electrode layers formed by forming a plurality of electrodes, and uses thereof, and a method and apparatus for producing the same. Background Art
[0004] For organopolysiloxane cured products having a polysiloxane skeleton, transparency, electrical insulation,
[0005] Excellent heat resistance, cold resistance, etc., can be introduced into the high dielectric functional group such as fluoroalkyl as desired
[0006] To improve electrical activity, and can be easily processed into film or sheet form, so it is used in various electrical / electronic
[0007] The adhesive film of the device or the electroactive film of the transducer device such as the actuator is used for various
[0008] These organopolysiloxane cured products are classified into hydrosilylation reaction according to their curing mechanism.
[0009] The curing type, condensation reaction curing type, peroxide curing type, etc. In particular, by leaving it at room temperature
[0010] It cures quickly by heating or curing without producing by-products, so the hydrosilylation reaction curing type solid
[0011] The organopolysiloxane cured product film of the chemically active organopolysiloxane composition is commonly used.
[0012] On the other hand, in the use of organopolysiloxane cured film as electronic materials such as touch panels,
[0013] Electronic components for display devices, especially transducer materials such as sensors and actuators, require
[0014] An electrode layer is provided on the electroactive film as a dielectric layer.
[0015] It is proposed that a conductive filler is added to a silicone elastomer matrix having excellent flexibility.
[0016] An electrode layer with an agent is formed to form an electrode layer having excellent followability to the dielectric layer.
[0017] However, when it is desired to form a film containing a polysiloxane having an electroactive film on a cured film of an organopolysiloxane,
[0018] In the case of an electrode layer containing a conductive filler, in particular, with the displacement of the dielectric layer (e.g.
[0019] expansion and contraction of the actuator, etc.), resulting in interfacial peeling between the dielectric layer and the electrode layer, which may be related to the conduction of electricity.
[0020] Defects and reduced reliability as an actuator. The applicant of this case proposed in Patent Document 1, etc.:
[0021] On the organopolysiloxane cured film as the electroactive film, a solid containing a conductive filler is applied.
[0022] A dielectric layer / electrode layer forming organopolysiloxane composition is provided, thereby forming an electrode layer as an organopolysiloxane cured product film on the electroactive film (= dielectric layer), and it is proposed that: as a transducer material for an actuator, in order to improve the followability of the electrode surface, a laminate of functional groups that participate in a common curing reaction for forming chemical bonds at the interface is used in the dielectric layer / electrode layer forming organopolysiloxane composition (Patent Document 2).
[0023] However, in recent years, the use of transducers such as actuators has gradually expanded to a wide temperature range including low to high temperatures. In particular, when used for transducers with large physical displacements, it is also required to maintain high conductivity, and even when used in a wide temperature range including high temperatures above 100°C, the viscoelasticity does not change significantly, and the electrode layer has excellent adhesion to the dielectric layer, tracking properties, and shape retention.
[0024] Prior art literature
[0025] Non-patent literature
[0026] Non-patent literature 1: Kujawski, M.; Pearse, JD; Smela, E. Carbon 2010, 48, 2409-2417.
[0027] Non-patent document 2: Rosset, S.; Shea, HR Appl. Phys. A 2013, 110, 281-307.
[0028] Patent Literature
[0029] Patent Document 1: International Patent Publication No. WO2014 / 105959
[0030] Patent Document 2: International Patent Publication No. WO2022 / 004462 Summary of the invention
[0031] Problems to be solved by the invention
[0032] The present invention is completed to solve the above-mentioned problems, and its purpose is to provide an electrode layer forming composition, a laminate using the same, its use and a manufacturing method, which can be applied to various processes including an electrode printing process (printing). Even if the obtained electrode is used in a wide temperature range including high temperatures above 100°C, its viscoelasticity will not change significantly, and its heat resistance, durability, adhesion to the dielectric layer, tracking and shape retention are significantly excellent. Even when using a transducer such as an actuator that is based on a high degree of physical displacement, it is not easy to produce problems such as peeling and defects of the electrode layer, and it is possible to form an electrode layer with viscoelastic properties that are sufficient for practical use.
[0033] Solutions for solving problems
[0034] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by an electrode layer forming curable organopolysiloxane composition, thereby completing the present invention, wherein the composition comprises: (A) a chain organopolysiloxane having curing reactive functional groups containing carbon-carbon double bonds at least at both ends of the molecular chain; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene and containing R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 Siloxane units (Q units) shown in the composition; and (E) conductive particles, wherein the composition is non-flowable at 25°C and has heat melting properties, the content of component (B) in the composition is less than 45% by mass relative to the entire composition, and it is particularly preferred that the conductive particles are particles of conductive carbon containing at least one selected from carbon nanotubes (CNTs), conductive carbon black, graphite and vapor grown carbon (VGCF), and the composition contains: component (A), component (B) and optionally (BX) an organopolysiloxane resin, wherein the organopolysiloxane resin contains R3SiO in a molecule having a weight average molecular weight of less than 5000 in terms of standard polystyrene. 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The content of the siloxane unit (Q unit), component (A), component (B) and component (BX) in the entire composition is in the range of 50 to 95% by mass, and the mass ratio of component (A) to component (B) is in the range of 100:0 to 50:50.
[0035] From the perspective of solving the problem, the electrode layer-forming curable organopolysiloxane composition involved in the present invention can achieve viscoelasticity and excellent conductivity of the obtained electrode layer, so as (E) conductive particles, it is particularly preferred to use a certain amount of fibrous conductive carbon such as single-walled carbon nanotubes (SWCNT).
[0036] In addition, the above-mentioned problems are solved by a laminate having a structure in which an electrode layer (L2) obtained by a curing reaction of the above-mentioned electrode layer-forming curable organopolysiloxane composition is laminated on at least one side of an organopolysiloxane cured film (L1) as a dielectric layer, and its use (including a transducer member, a transducer, an electronic component or a display device).
[0037] Furthermore, the above-mentioned problems are solved by the following method for manufacturing a laminate and a method for forming an electrode layer in a transducer member including the manufacturing method, the manufacturing method comprising: step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film state, thereby obtaining an organopolysiloxane cured product film as a dielectric layer; step II: simultaneously with step I or after step I, a step of applying an electrode layer obtained by a curing reaction of the above-mentioned electrode layer-forming curable organopolysiloxane composition on the organopolysiloxane cured product film involved in step I or on a precursor thereof, thereby forming the electrode layer by the curing reaction thereof.
[0038] Effects of the Invention
[0039] According to the present invention, it is possible to provide an electrode layer forming composition, a laminate using the same, and its use and manufacturing method. The electrode layer forming composition can be applied to various processes including printing, and the electrode obtained by the curing reaction does not change its viscoelasticity significantly even when used in a wide temperature range including high temperatures of 100°C or above, and is significantly excellent in heat resistance, durability, adhesion to the dielectric layer, tracking and shape retention. Even when using a transducer that is based on a high degree of physical displacement such as an actuator, it is not easy to cause the problem of peeling and defects of the electrode layer, and it is possible to form an electrode layer with viscoelastic properties sufficient for practical use. In particular, according to the present invention, it is possible to provide a laminate and a manufacturing method thereof that are not easy to cause interface peeling with an organopolysiloxane cured film as a dielectric layer, poor current conduction, and excellent reliability in the use of actuators, etc., even when used in a wide temperature range including high temperatures of 100°C or above. DETAILED DESCRIPTION
[0040] [Electrode layer forming curable organopolysiloxane composition]
[0041] First, the electrode layer forming curable organopolysiloxane composition (hereinafter referred to as "the present composition") is described. The present composition is characterized in that it comprises: (A) a chain organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene and containing a R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane unit (Q unit) shown; and (E) conductive fine particles, wherein the composition is non-fluid and has heat-melting properties at 25°C, and the content of component (B) in the composition is less than 45% by mass relative to the entire composition.
[0042] Here, the present composition is a composition in which the amount of the organopolysiloxane resin having a large average molecular weight as the above-mentioned component (B) is small, and an organopolysiloxane resin having an average molecular weight smaller than that of the component (B) may be used or used together. Specifically, the present composition is preferably an electrode layer forming curable organopolysiloxane composition, which contains the component (A), the component (B) and the optional (BX) organopolysiloxane resin, wherein the above-mentioned organopolysiloxane resin has a molecular weight of less than 5000 in terms of standard polystyrene and contains R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The content of the siloxane unit (Q unit), component (A), component (B) and component (BX) in the entire composition is in the range of 50 to 95% by mass, and the mass ratio of component (A) to component (B) is in the range of 100:0 to 50:50.
[0043] The present composition has curing reactivity, and in particular, component (A) is a curing reactive functional group containing a carbon-carbon double bond, so it preferably has curing reactivity by hydrosilylation reaction, and in addition to component (A), component (B) and component (E), it further preferably contains: (C) an amount of 0.1 to 1.5 mol of silicon-bonded hydrogen atoms in the present component relative to 1 mol of the total amount of carbon-carbon double bonds in the organohydrogenpolysiloxane composition having at least two silicon-bonded hydrogen atoms in the molecule, and (D) an effective amount of a hydrosilylation reaction catalyst. Furthermore, in practical terms, it may further contain a component selected from (F) a reinforcing filler, (G) a curing retarder, and (H) a tackifier.
[0044] The electrode layer composed of the organopolysiloxane cured product obtained by the curing reaction of the present composition has excellent viscoelasticity at high temperatures, and can easily obtain a shear storage modulus (G') of 1.0×10 4 ~1.5×10 6 In particular, the present composition can preferably obtain an electrode layer having a shear storage modulus (G') of 2.0×10 4 ~1.0×10 6 Pa range of electrode layer.
[0045] The viscoelasticity of the electrode layer obtained using the present composition at room temperature is not particularly limited, but after the electrode layer is formed, the shear storage modulus (G' 25℃ ) can be 1.0×10 5 ~7.5×10 6 Pa range, even at room temperature, it is possible to achieve practically sufficient viscoelasticity of the electrode layer. In addition, from the viewpoint of the viscoelasticity of the electrode layer obtained using the present composition, the value of tanδ of the composition at 25°C before or after electrode formation (especially after curing) is particularly preferably 0.30 or more, and in particular, the value of tanδ of the composition before electrode formation is preferably in the range of 0.35 to 0.99. This is because, when the viscoelasticity of the present composition or the electrode layer composed thereof satisfies the above conditions, it is not easy to cause the problem of peeling and defects of the electrode layer, and an electrode layer with practically sufficient viscoelastic properties can be formed.
[0046] [Ingredients (A)]
[0047] Component (A) is a chain organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain, and is a component that achieves good viscoelasticity at high temperatures in the electrode layer obtained by the curing reaction. Such a chain organopolysiloxane can be exemplified by a substance having a straight chain or a branched structure with a few branch points, but a straight chain organopolysiloxane is particularly preferred in practice. In the case of using a highly branched organopolysiloxane, it is sometimes impossible to achieve heating meltability, or the electrode layer is hardened and viscoelasticity cannot be obtained, which is not preferred.
[0048] Component (A) has a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain. The curing reactive functional group containing a carbon-carbon double bond is selected from alkenyl groups having 2 to 20 carbon atoms such as vinyl; and curing reactive groups in groups containing (meth)acryloyl groups such as 3-acryloxypropyl and 3-methacryloxypropyl, and alkenyl groups having 2 to 6 carbon atoms are particularly preferred.
[0049] The chain organopolysiloxane in component (A) may contain a group selected from a monovalent hydrocarbon group having no carbon-carbon double bond in the molecule, a hydroxyl group, and an alkoxy group having 1 to 3 carbon atoms. In addition, in the monovalent hydrocarbon group, part of the hydrogen atoms may be substituted by a halogen atom or a hydroxyl group. Industrially, methyl, phenyl, hydroxyl, and alkoxy groups are preferred.
[0050] Preferably, component (A) has at both ends of its molecular chain
[0051] (Alk)R 2 2SiO 1 / 2
[0052] (wherein Alk is an alkenyl group having 2 or more carbon atoms), and the other siloxane units are substantially composed only of R 2 2SiO 2 / 2 A linear organopolysiloxane composed of the siloxane units shown in the formula: 2 The siloxane polymerization degree of component (A) is within the range of 7 to 1002, including the terminal siloxane unit, and may be within the range of 102 to 902.
[0053] [Component (B) and component (BX)]
[0054] The component (B) is characterized in that it is an organopolysiloxane resin, which uses organic solvents such as toluene and xylene, and has a weight average molecular weight of 5000 or more in standard polystyrene conversion measured by GPC (gel permeation chromatography), and has M units and Q units in the molecule. In the present composition, in addition to using component (A), the usage of component (B) is below a certain amount. This is because component (B) is an MQ type organopolysiloxane resin with a molecular weight of more than a certain amount, but when its deployment amount is large, the temperature dependence of the viscoelasticity of the electrode layer obtained by the curing reaction of the present composition, especially at high temperatures, becomes large. On the other hand, by using component (B) together, the heat resistance, durability, adhesion to the dielectric layer, tracking and shape retention of the electrode are sometimes improved, so if it is within the range of an appropriate usage amount, the performance of the electrode layer involved in the present invention can sometimes be improved.
[0055] The first characteristic of component (B) is that it is a high molecular weight organopolysiloxane resin having a weight average molecular weight of 5000 or more. From the viewpoint of the temperature dependence of the viscoelasticity of the obtained cured product and the shape retention of the obtained electrode, the weight average molecular weight of component (B) is preferably 5500 or more, 6000 or more, and industrially, it is particularly preferably in the range of 5500 to 100,000, 6000 to 50,000.
[0056] On the other hand, the weight average molecular weight of component (B) is less than the above lower limit (i.e., a low molecular weight organopolysiloxane resin), that is, the following organopolysiloxane resin (BX) may be formulated into the composition of the present invention: a molecule having a weight average molecular weight of less than 5000 in terms of standard polystyrene and containing R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane unit (Q unit) shown in FIG. 1 is a siloxane unit (Q unit) shown in FIG. 1 . Since the component (BX) has a small molecular weight, even if it is formulated in the electrode layer obtained by the curing reaction of the present composition, the temperature dependence of the viscoelasticity at high temperature is not too large, and stable performance can sometimes be achieved. That is, in the present invention, the content of the component (B) which is a high molecular weight organopolysiloxane resin having a molecular weight of more than a certain value has a particularly large influence on the performance of the electrode layer at high temperature, and it is allowed to formulate a low molecular weight component (BX) in a range of more than 45% by mass.
[0057] The component (B) or the component (BX) has R3SiO in the molecule. 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane unit (Q unit) shown may also optionally contain a siloxane selected from R2SiO 2 / 2 (D unit) and RSiO 3 / 2 The siloxane unit in (T unit), the component (B) or the component (BX) is composed of the following average unit formula:
[0058] (R3SiO 1 / 2 )p(R2SiO 2 / 2 )q(RSiO 3 / 2 )r(SiO 4 / 2 )s(XO 1 / 2 )t shown organopolysiloxane resin.
[0059] R is a monovalent organic group, and may be a curing reactive group containing a carbon-carbon double bond, or may be a group selected from a monovalent hydrocarbon group, a hydroxyl group, and an alkoxy group that does not have a carbon-carbon double bond in the molecule.
[0060] Specifically, the curing reactive group containing a carbon-carbon double bond as R can be exemplified by a curing reactive group selected from the following: alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl, and dodecenyl; groups containing an acryl group, such as 3-acryloxypropyl and 4-acryloxybutyl; and groups containing a methacryl group, such as 3-methacryloxypropyl and 4-methacryloxybutyl.
[0061] Similarly, the monovalent hydrocarbon group not having a carbon-carbon double bond as R includes: alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, anthracenyl, phenanthryl, and pyrenyl; aralkyl groups such as benzyl, phenethyl, naphthylethyl, naphthylpropyl, anthracenylethyl, phenanthrylethyl, and pyrenylethyl; and groups in which the hydrogen atoms of these aryl or aralkyl groups are substituted by alkyl groups such as methyl and ethyl; alkoxy groups such as methoxy and ethoxy; chlorine atoms, bromine atoms, etc.
[0062] In the above average unit formula, X is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and OX is a hydroxyl group or an alkoxy group having 1 to 3 carbon atoms. Such a hydrolyzable functional group may be a hydroxyl group remaining in the resin during the synthesis of the organopolysiloxane resin, or may be a structure in which the hydroxyl group in the resin is sealed by treatment with a silazane compound or the like during synthesis.
[0063] Here, it is preferred that p is a positive number, q and r are 0 or positive numbers, s is a positive number, t / (p+q+r+s) is a number in the range of 0 to 0.4, (p+q) / (r+s) is preferably in the range of 0.5 to 2.0, and q and r may be 0, and the organic polysiloxane resin may consist only of M units and Q units.
[0064] The component (B) or component (BX) in the present invention may be selected from
[0065] (B1) an organopolysiloxane resin having a curing reactive group containing a carbon-carbon double bond in the molecule, and
[0066] (B2) an organopolysiloxane resin having no curing reactive group containing a carbon-carbon double bond in the molecule
[0067] One or more organopolysiloxane resins, but from the perspective of improving the curing reactivity and the temperature dependence of the viscoelasticity of the obtained electrode layer, the shape retention of the dielectric layer, etc., these components (B1) and components (B2) may also be included simultaneously. Specifically, component (B1) and component (B2) can be used together in a mass ratio of 5:95 to 95:5, or in a mass ratio of 5:95 to 50:50. It should be noted that when component (BX) is included, at least a portion of component (B1) and component (B2) is an organopolysiloxane resin having a weight average molecular weight of less than 5000 in standard polystyrene conversion.
[0068] Examples include organopolysiloxane resins containing alkenyl groups. The organopolysiloxane resin as component (B1) preferably has the above-mentioned weight average molecular weight, has the above-mentioned M units and Q units, and at least a portion of R is an alkenyl group such as vinyl or hexenyl, and the content of the vinyl (CH2=CH-) group is in the range of 1.0 to 5.0% by mass, preferably 1.2 to 3.5% by mass. It should be noted that R other than the alkenyl group is not particularly limited, but in industry, other R may be an alkyl group such as methyl and an aryl group such as phenyl. It should be noted that the M unit, the Q unit, and the optionally included (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0069] The organopolysiloxane resin as component (B2) is an organopolysiloxane resin that preferably has the above-mentioned weight average molecular weight, has the above-mentioned M unit and Q unit, and R is a group selected from alkyl groups such as methyl and aryl groups such as phenyl, and does not have a curing reactive group containing a carbon-carbon double bond in the molecule. It should be noted that the M unit, Q unit, and the optionally contained (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0070] The composition of the present invention comprises component (A), component (B) and optionally (BX) an organopolysiloxane resin, wherein the organopolysiloxane resin has a molecular weight of less than 5000 in terms of standard polystyrene and contains R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2The siloxane units (Q units) shown in the above-mentioned composition do not contain the component (B) which is an organopolysiloxane resin having a large molecular weight, or the content thereof is less than 45% by mass. It is particularly preferred that the content of the component (B) in the entire composition is less than 0 to 45% by mass, 0 to 40% by mass, or 0 to 35% by mass. In addition, the weight average molecular weight of the component (BX) is less than 5000, preferably in the range of 500 to 4500, or in the range of 1000 to 4000. It should be noted that in aspects other than the molecular weight, it may be the same organopolysiloxane resin as the component (B).
[0071] In order to adjust the viscoelasticity, durability, adhesion to the dielectric layer, followability and shape retention of the electrode layer obtained by the curing reaction of the present composition, and reduce its temperature dependence at high temperatures of 100° C. or higher, the content of component (A), component (B) and component (BX) in the entire composition is in the range of 50 to 95% by mass, preferably 55 to 90% by mass, and more preferably 60 to 90% by mass, and the mass ratio of component (A) to component (B) can be in the range of 100:0 to 50:50, preferably in the range of 95:5 to 50:50.
[0072] [Ingredient (C)]
[0073] Component (C) is a crosslinking agent that can react with a curing reactive group containing a carbon-carbon double bond in component (A) or component (B) / (BX) in the presence of component (D) to form a cured product by hydrosilylation reaction.
[0074] Examples of such component (C) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, methylhydrogenpolysiloxane terminated at both ends of the molecular chain by trimethylsiloxy, dimethylsiloxane / methylhydrogensiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, dimethylpolysiloxane terminated at both ends of the molecular chain by dimethylhydrogensiloxy, dimethylsiloxane / methylhydrogensiloxane copolymer terminated at both ends of the molecular chain by dimethylhydrogensiloxy, methylhydrogensiloxane / diphenylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, hydrolysis condensation product of trimethoxysilane, (CH3)2HSiO 1 / 2 Unit and SiO 4 / 2 The copolymer consists of (CH3)2HSiO 1 / 2 Unit, SiO 4 / 2 Unit and (C6H5)SiO 3 / 2The invention also includes copolymers composed of these units and mixtures of two or more thereof.
[0075] The amount of component (C) used may be in the range of 0.1 to 5.0 mol, 0.1 to 1.5 mol, or 0.1 to 1.20 mol of silicon-bonded hydrogen atoms relative to 1 mol of carbon-carbon double bonds in the composition. In particular, if the amount of component (C) used is below the upper limit, the mechanical strength and temperature dependence of the cured product can be easily designed within a practically appropriate range, and an electrode having better followability of the electrode layer to the dielectric layer and better shape retention can be easily obtained.
[0076] [Ingredient (D)]
[0077] Component (D) is a catalyst for the curing reactive group containing a carbon-carbon double bond in the present composition and for promoting the hydrosilylation reaction of component (C), and examples thereof include platinum-based catalysts, rhodium-based catalysts, palladium-based catalysts, nickel-based catalysts, iridium-based catalysts, ruthenium-based catalysts, and iron-based catalysts, preferably platinum-based catalysts. Examples of the platinum-based catalyst include platinum fine powder, platinum black, platinum-supported silica fine powder, platinum-supported activated carbon, chloroplatinic acid, an alcohol solution of chloroplatinic acid, an olefin complex of platinum, an alkenyl siloxane complex of platinum, and platinum alkenyl siloxane complexes, and platinum alkenyl siloxane complexes are particularly preferred. Examples of the alkenylsiloxane include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxanes in which a part of the methyl groups of these alkenylsiloxanes are substituted with ethyl groups, phenyl groups, etc., and alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes are substituted with allyl groups, hexenyl groups, etc. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred from the viewpoint of good stability of the platinum-alkenylsiloxane complex. Furthermore, from the viewpoint of being able to improve the stability of the platinum-alkenylsiloxane complex, it is preferred to add alkenylsiloxanes such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3-diallyl-1,1,3,3-tetramethyldisiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane, 1,3-divinyl-1,1,3,3-tetraphenyldisiloxane, and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and organosiloxane oligomers such as dimethylsiloxane oligomers to the complex, and it is particularly preferred to add alkenylsiloxanes. In addition, from the perspective of improving the workability and the pot life of the composition, these hydrosilylation reaction catalysts may also be thermoplastic resin particles containing hydrosilylation reaction catalysts as catalysts dispersed or encapsulated in thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, and in particular thermoplastic resin particles containing hydrosilylation reaction catalysts containing platinum. It should be noted that as a catalyst that promotes the hydrosilylation reaction, non-platinum metal catalysts such as iron, ruthenium, and iron / cobalt can be used.
[0078] In particular, when the composition of the present invention is a composition for forming an electrode by curing, from the viewpoint of improving the stability, workability and pot life of the composition during production, at least a part of the component (D) may be (D1) thermoplastic resin microparticles containing a hydrosilylation reaction catalyst containing platinum, and this is preferred. Such a component (D1) may be any of the following structures: microparticles in which a platinum-based hydrosilylation reaction catalyst is dissolved or dispersed in a thermoplastic resin; or microcapsule microparticles having a structure in which a platinum-based catalyst is contained as a core in an outer shell of a thermoplastic resin. As the platinum-based catalyst, the same platinum alkenylsiloxane complex as described above can be exemplified. In addition, the thermoplastic resin is not particularly limited as long as it does not substantially permeate the platinum-based catalyst and does not substantially dissolve in the organopolysiloxane which is the main component of the present composition at least during production and storage of the present composition, but the softening point or glass transition point of the thermoplastic resin is preferably 80°C or more, and more preferably 120°C or more. Specifically, silicone resins, polysilane resins, epoxy resins, acrylic resins, and methylcellulose polycarbonate resins can be preferably used. The softening point is the temperature at which the resin begins to flow due to its own weight or its own surface tension, and can be measured by observing the crushed particles under a microscope while raising the temperature at a certain speed. In addition, the glass transition point can be measured by DSC (Differential Scanning Calorimeter). In the present invention, it is preferred that either the softening point or the glass transition point is above 120°C. This is because if the softening point or the glass transition point of the thermoplastic resin is lower than 120°C, the platinum component may begin to dissolve in the process of uniformly mixing the present composition described later. In addition, the average particle size of the thermoplastic microparticles containing the platinum catalyst is not limited, but is preferably in the range of 0.1 to 500 μm, and more preferably in the range of 0.3 to 100 μm. This is because it is difficult to prepare thermoplastic resin microparticles containing a platinum catalyst having an average particle size less than the lower limit of the above range, and on the other hand, if the upper limit of the above range is exceeded, the dispersibility in the present composition is reduced.
[0079] The method for preparing such thermoplastic resin microparticles containing a hydrosilylation reaction catalyst containing platinum is not limited, and examples thereof include: chemical methods such as the conventionally known interfacial polymerization method and in-situ polymerization method; physical / mechanical methods such as the coagulation method and the in-liquid drying method. In particular, from the viewpoint of being easier to obtain microcapsule microparticles with a narrow particle size distribution, it is preferred to use the in-liquid drying method and the gas phase drying method using a spray dryer or the like. The microparticles obtained by these methods can be used directly, but in order to obtain a composition with excellent storage stability, it is preferred to wash the microparticles with an appropriate cleaning solvent to remove the platinum catalyst attached to the surface. Here, an appropriate cleaning solvent refers to a cleaning solvent having the property of not dissolving the thermoplastic resin but dissolving the platinum catalyst. As such a cleaning solvent, for example, alcohols such as methanol and ethanol; low molecular weight organopolysiloxanes such as hexamethyldisiloxane, etc. can be cited. The ratio of the catalyst for hydrosilylation reaction to the thermoplastic resin varies greatly depending on the method for producing the granular material, and therefore cannot be particularly limited, but the content of the platinum-based catalyst relative to the thermoplastic resin is preferably 0.01% by mass or more. This is because, when the content of the platinum-based catalyst is less than 0.01% by mass, if the thermoplastic resin particles containing the platinum-based catalyst that are contained in the present composition are not contained in large quantities, the physical properties of the cured product are impaired by the present composition.
[0080] The amount of the hydrosilylation reaction catalyst as component (D) added is a catalytic amount, preferably 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm in terms of metal atoms by mass relative to the entire composition.
[0081] A part or all of the component (D) does not show activity without irradiation with high energy rays, but may be a catalyst for hydrosilylation reaction that shows activity in the composition by irradiation with high energy rays, a so-called high energy ray activated catalyst or a photoactivated catalyst. By using such a component (D), the composition as a whole can achieve the following characteristics: it can be cured even at low temperatures by irradiation with high energy rays as a trigger, has excellent storage stability, and is easy to control the reaction, so it is excellent in workability.
[0082] Examples of high-energy rays include ultraviolet rays, gamma rays, X-rays, alpha rays, electron beams, and the like. In particular, ultraviolet rays, X-rays, and electron beams irradiated by commercially available electron beam irradiation devices are included. Ultraviolet rays are preferred from the perspective of catalyst activation efficiency, and ultraviolet rays with a wavelength of 280 to 380 nm are preferred from the perspective of industrial utilization. In addition, the irradiation amount varies depending on the type of high-energy ray-activated catalyst. In the case of ultraviolet rays, the cumulative irradiation amount at a wavelength of 365 nm is preferably 100 mJ / cm2 ~100J / cm 2 within the range.
[0083] Specific examples of component (D) include (methylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)trimethylplatinum (IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)dimethylethylplatinum (IV), (cyclopentadienyl)dimethylacetylplatinum (IV), (trimethylsilylcyclopentadienyl)trimethylplatinum (IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum (IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum (IV), trimethyl(acetylacetylacetonate)platinum (IV), trimethyl(3,5-heptadienyl)trimethylplatinum (IV), and trimethyl(3,5-heptadienyl)trimethylplatinum (IV). bis(2,4-pentanedione)platinum(II), bis(2,4-hexanedione)platinum(II), bis(2,4-heptanedione)platinum(II), bis(3,5-heptanedione)platinum(II), bis(1-phenyl-1,3-butanedione)platinum(II), bis(1,3-diphenyl-1,3-propanedione)platinum(II), bis(hexafluoroacetylacetylacetonate)platinum(II), among which (methylcyclopentadienyl)trimethylplatinum(IV) and bis(2,4-pentanedione)platinum(II) are preferred from the aspects of versatility and ease of acquisition.
[0084] The amount of the high energy ray activated catalyst used as component (D) is an effective amount and is not particularly limited, as long as it is an amount that promotes the curing of the composition of the present invention. Specifically, the metal atoms in the catalyst are 0.01 to 1,000 ppm by mass relative to the sum of the components (A) to (C) (the whole is set to 100% by mass), and preferably the platinum metal atoms in the component (D) are in an amount within the range of 0.1 to 500 ppm.
[0085] [Ingredient (E)]
[0086] Component (E) is conductive particles, and there is no particular limitation as long as it is a substance that can provide conductivity to the electrode layer formed using the composition of the present invention. It should be noted that, regarding the electrode layer containing conductive particles, for example, in the international patent publication WO2014 / 105959 of the applicant of the present case, etc., it is proposed, but in particular, no content related to carbon nanotubes (CNTs) is disclosed.
[0087] Specifically, component (E) includes conductive carbon such as carbon nanotubes (CNT), conductive carbon black, graphite (the present invention also includes graphite coated with a conductive material such as metal such as nickel graphite), vapor grown carbon (VGCF), etc.; metal powders such as platinum, gold, silver, copper, nickel, tin, zinc, iron, and aluminum; further examples include antimony-doped tin oxide, phosphorus-doped tin oxide, needle-shaped titanium oxide coated with tin oxide / antimony, tin oxide, indium oxide, antimony oxide, zinc antimonate, and pigments coated with tin oxide on the surface of carbon and graphite whiskers; pigments coated with at least one conductive metal oxide selected from the group consisting of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), phosphorus-doped tin oxide, and nickel oxide; conductive pigments containing tin oxide and phosphorus on the surface of titanium dioxide particles, etc., and these can also be treated with various surface treatment agents. These can be used alone or in combination of two or more. In order to uniformly disperse these conductive fine particles in the composition, they may be kneaded in advance with a part or all of the components (A) to (C) used in the composition and formulated in the composition in the form of a composite.
[0088] Furthermore, the conductive inorganic particles can also be particles of conductive materials such as metals coated on the surface of fibers such as glass fibers, silica alumina fibers, alumina fibers, carbon fibers, and needle-shaped reinforcing materials such as aluminum borate whiskers and potassium titanate whiskers, and inorganic fillers such as glass beads, talc, mica, graphite, wollastonite, and dolomite.
[0089] In the composition involved in the present invention, at least a part of component (E) is preferably fine particles containing at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite and vapor grown carbon (VGCF), and these conductive fine particles have the following advantages: excellent uniform dispersibility in the organopolysiloxane composition, excellent temperature dependence of the viscoelasticity of the electrode layer obtained using the electrode layer forming curable organopolysiloxane composition, and can effectively improve the followability and shape retention of the electrode layer to the dielectric layer.
[0090] In the composition of the present invention, at least a part or all of component (E) is preferably carbon nanotubes (CNTs). CNTs may be single-layer, double-layer, or multi-layer, and their particle size is not particularly limited, but conductive particles comprising (E1) single-walled carbon nanotubes (SWCNTs) are particularly preferred.
[0091] Single-walled carbon nanotubes (SWCNTs) are a special type of carbon material known as a one-dimensional material. Single-walled carbon nanotubes are composed of graphene sheets, which are wound into a hollow tube with a wall of one atom thickness. By having such a chemical structure and size, single-walled carbon nanotubes have a tendency to show particularly excellent mechanical, electrical, thermal and optical properties even among other conductive carbons such as acetylene black. In particular, even if used in small amounts, the volume resistivity of the obtained electrode layer will be effectively reduced, and the mechanical strength such as the elongation and tensile strength of the electrode layer at break can be maintained without damaging the electrode layer, thereby achieving the advantages of being able to particularly effectively improve the tracking and shape retention of the electrode layer to the dielectric layer in addition to the high performance and high strength of the electrode layer, which includes improving the energy density of the electrode layer.
[0092] The average outer diameter of the single-walled carbon nanotubes is not particularly limited, but is preferably 2.5 nm or less. It is more preferably 1.0 to 2.5 nm, further preferably 1.1 to 2.0 nm, and particularly preferably 1.2 to 1.8 nm. The average outer diameter of the single-walled carbon nanotubes can be obtained from the light absorption spectrum of the single-walled carbon nanotubes obtained by ultraviolet visible near infrared spectroscopy (UV-Vis-NIR), Raman spectrum, or transmission electron microscope (TEM) image.
[0093] The average fiber length of the single-walled carbon nanotubes is preferably less than 100 μm. It is more preferably 0.1 to 50 μm, further preferably 0.5 to 20 μm, and particularly preferably 1 to 10 μm. The average fiber length of the single-walled carbon nanotubes can be obtained as follows: an AFM image of the single-walled carbon nanotubes is obtained using an atomic force microscope (AFM), or a TEM image of the single-walled carbon nanotubes is obtained using a transmission electron microscope (TEM), the length of each single-walled carbon nanotube is measured, and the total length is divided by the number of single-walled carbon nanotubes measured.
[0094] The G / D ratio of single-walled carbon nanotubes measured by Raman spectroscopy (wavelength 532nm) is preferably 2 or more. It is more preferably 2 to 250, further preferably 5 to 250, particularly preferably 10 to 220, and most preferably 40 to 180. The G / D ratio refers to the intensity ratio (G / D) of the G band and the D band of the Raman spectrum of the single-walled carbon nanotube. The higher the G / D ratio of the single-walled carbon nanotube, the higher the crystallinity of the single-walled carbon nanotube, and the fewer carbon nanotubes with impurity carbon and defects.
[0095] Single-walled carbon nanotubes (SWCNTs) can be obtained as commercial products. For example, in the present invention, TUBALL(TM)MATRIX 601 (polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 602 (vinyl ether-terminated polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 201 (aliphatic glycidyl ester containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 202 (aliphatic carboxylic acid ester derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 204 (methacrylate derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 301 (ethoxylated alcohol containing 10% by mass of single-walled carbon nanotubes) (all manufactured by Kusumoto Chemicals Co., Ltd.), etc. can be cited.
[0096] Part or all of the above-mentioned conductive particles may be conductive particles whose surfaces are partially or entirely treated by an organosilicon compound. Examples of organosilicon compounds are low molecular weight organosilicon compounds such as silane, silazane, siloxane or the like; and organosilicon polymers or oligomers such as polysiloxane, polycarbosiloxane or the like. Examples of preferred silanes are so-called silane coupling agents. Representative examples of such silane coupling agents are alkyltrialkoxysilanes (methyltrimethoxysilane, vinyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane or the like), trialkoxysilanes containing organic functional groups (glycidoxypropyltrimethoxysilane, epoxycyclohexylethyltrimethoxysilane, methacryloxypropyltrimethoxysilane, aminopropyltrimethoxysilane or the like). Preferred siloxanes and polysiloxanes include: hexamethyldisiloxane, 1,3-dihexyltetramethyldisiloxane, trialkoxysilyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated dimethylvinyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated organic functional group single-terminated polydimethylsiloxane, trialkoxysilyl doubly terminated polydimethylsiloxane, organic functional group doubly terminated polydimethylsiloxane or the like. When using siloxane, the number n of siloxane bonds is preferably in the range of 2 to 150. In addition, siloxane is not necessarily a main chain, but may be a substance obtained by siloxane modification of an organic polymer. As an example, silicone-modified acrylic polymers can be cited. Preferred examples of silazanes are hexamethyldisilazane, 1,3-dihexyltetramethyldisilazane or the like. Preferred polycarbosiloxanes are exemplified by polymers having Si-CC-Si bonds in the polymer backbone.
[0097] The amount of component (E) can be appropriately designed according to the conductivity (i.e., volume resistivity), mechanical strength, and shape retention of the obtained electrode layer. However, in practice, the volume fraction of the conductive fine particles (E) relative to the entire composition is preferably in the range of 0.003 to 0.50, and more preferably in the range of 0.003 to 0.25. Within the range of the amount of component (E), the volume resistivity of the electrode layer obtained using the present composition is 10 3 Ω·cm or less, preferably 10 to 10 3 In the range of Ω·cm, there is an advantage that an electrode layer showing excellent conductivity can be designed, and in particular, when a part of component (E) is fine particles containing conductive carbon, in particular, when a part of component (E) is single-walled carbon nanotubes (SWCNT), there are the following advantages: the volume resistivity of the electrode layer is effectively reduced to achieve excellent conductivity, and the mechanical strength of the electrode layer such as elongation and tensile strength at break is not impaired, and its viscoelasticity can achieve excellent temperature dependence. In particular, the volume fraction of the single-walled carbon nanotube (SWCNT) relative to the entire composition is preferably in the range of 0.0015 to 0.25.
[0098] [Ingredients (F)]
[0099] Component (F) is a reinforcing filler, which can sometimes improve the mechanical strength of the electrode layer obtained by the curing reaction of the present composition. Specifically, it is preferably an average primary particle size of less than one or more reinforcing inorganic particles of 50nm, which can be exemplified by: fumed silica, wet silica, crushed silica, calcium carbonate, diatomaceous earth, finely crushed quartz, various metal oxide powders other than aluminum oxide / zinc oxide, glass fiber, carbon fiber, etc., and these are treated with one or more organosilicon compounds described later and obtained. The shape is not particularly limited, and the reinforcing inorganic particles of optional shapes such as particle-shaped, plate-shaped, needle-shaped, and fibrous can be used.
[0100] Preferred examples of component (F) include hydrophilic or hydrophobic fumed silica or metal oxide composites thereof having an average primary particle size of 10 nm or less and capable of partial aggregation. Furthermore, from the perspective of improving dispersibility, the fumed silica or metal oxide composites thereof are preferably treated with the above-mentioned organosilicon compound. Two or more of these reinforcing inorganic particles may also be used in combination.
[0101] The BET specific surface area of component (F) can be appropriately selected, but may be 10 m 2 / g or more, and can also be 10 to 1000 m 2 / g. Furthermore, as component (F), two or more reinforcing fillers with different BET specific surface areas may be used together. For example, as component (F), (F1) having an average BET specific surface area of more than 100 m2 and surface treated with one or more organic silicon compounds may be used alone. 2 / g reinforcing fine particles or a composite thereof and (F2) surface-treated with one or more organic silicon compounds and having an average BET specific surface area of 10 to 100 m 2 The reinforcing fine particles or the composite thereof in the range of 100 wt % to 200 wt % can be used together with the component (F1) and the component (F2) at an optional ratio by mass.
[0102] Preferably, component (F) is surface treated with the above-mentioned organosilicon compound, and preferred organosilicon compounds include one or more selected from hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane. It should be noted that, within the scope of not hindering the technical effect of the present invention, surface treatment with a surface treatment agent other than the organosilicon compound may also be used together.
[0103] In the above-mentioned surface treatment, the ratio of the surface treatment agent to the total amount of the filler is preferably in the range of 0.1 mass % to 50 mass %, more preferably in the range of 0.3 mass % to 40 mass %. It should be noted that the treatment amount is the charge ratio of the filler to the surface treatment agent, and the remaining treatment agent is preferably removed after the treatment. In addition, when the treatment is performed as needed, there is no problem in using additives that promote or assist the reaction.
[0104] [Ingredient (G)]
[0105] Component (G) is a curing retarder, and in particular, when the present composition is cured by a hydrosilylation reaction, it can effectively suppress side reactions and further improve the storage stability and usable life of the composition of the present invention.
[0106] The curing retarder that can be used is not particularly limited in its structure and type, and can be selected from known hydrosilylation reaction inhibitors, for example: alkynols such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; enyne compounds such as 3-methyl-3-pentene-1-yne and 3,5-dimethyl-3-hexene-1-yne; low molecular weight siloxanes containing alkenyl groups such as tetramethyltetravinylcyclotetrasiloxane and tetramethyltetrahexenylcyclotetrasiloxane; alkynyloxysilanes such as methyl-tris(1,1-dimethyl-2-propynyloxy)silane and vinyl-tris(1,1-dimethylpropynyloxy)silane.
[0107] The amount of component (G) used is optional, but is preferably within a range of 1 to 10000 ppm by mass based on the entire composition.
[0108] [Ingredient (H)]
[0109] Component (H) is a tackifier, and examples thereof include an organic silicon compound having at least one alkoxy group bonded to a silicon atom in one molecule. Examples of the alkoxy group include: methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy, and methoxy is particularly preferred. In addition, as groups bonded to silicon atoms other than alkoxy groups in the organic silicon compound, examples thereof include: halogen-substituted or non-substituted monovalent hydrocarbon groups such as alkyl, alkenyl, aryl, aralkyl, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl; epoxycyclohexylalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl; monovalent organic groups containing an acryl group such as 3-methacryloxypropyl; and hydrogen atoms. The organosilicon compound preferably has a group that can react with an alkenyl group or a silicon-bonded hydrogen atom in the present composition, and specifically, preferably has a silicon-bonded hydrogen atom or an alkenyl group. In addition, it can provide good adhesion to various substrates, so the organosilicon compound preferably has at least one monovalent organic group containing an epoxy group in one molecule. As such an organosilicon compound, examples include: an organosilane compound, an organosiloxane oligomer, and an alkyl silicate. As the molecular structure of the organosiloxane oligomer or the alkyl silicate, examples include a linear, a linear having a part of a branched chain, a branched, a cyclic, and a reticular shape, and particularly preferably a linear, a branched, and a reticular shape. Examples of the organosilicon compound include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds each having at least one silicon-bonded alkenyl group or silicon-bonded hydrogen atom and silicon-bonded alkoxy group in one molecule; a silane compound having at least one silicon-bonded alkoxy group or a mixture of a siloxane compound and a siloxane compound each having at least one silicon-bonded hydroxyl group and silicon-bonded alkenyl group in one molecule; a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane; an organic compound having at least two alkoxysilyl groups in one molecule and containing bonds other than silicon-oxygen bonds between these silyl groups; and a siloxane compound having the general formula: R a n Si(OR b ) 4-n
[0110] (Where R ais a monovalent organic group containing an epoxy group, R b is an alkyl group having 1 to 6 carbon atoms or a hydrogen atom. n is a number in the range of 1 to 3)
[0111] The epoxy-containing silane or its partial hydrolysis condensate shown, the reaction mixture of the vinyl-containing siloxane oligomer (including the siloxane oligomer of chain or cyclic structure) and the epoxy-containing trialkoxysilane, methyl polysilicate, ethyl polysilicate, ethyl polysilicate containing epoxy group. The tackifier is preferably a low-viscosity liquid, and its viscosity is not limited, but preferably in the range of 1 to 500 mPa·s at 25°C. In addition, the content of the tackifier is not limited, but preferably in the range of 0.01 to 10 parts by mass relative to a total of 100 parts by mass of the present composition.
[0112] In the present invention, as a particularly preferred tackifier, a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane can be exemplified. Such a component is a component that improves the initial adhesion to various substrates, especially the low-temperature adhesion to unwashed adherends, during the formation of the electrode layer obtained using the present composition (after heating and melting and during curing). Such a reaction mixture is disclosed in Japanese Patent Publication No. 52-8854 and Japanese Patent Publication No. 10-195085.
[0113] Examples of alkoxysilanes having an amino group-containing organic group constituting such a component include aminomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)aminomethyltributoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and 3-anilinopropyltriethoxysilane.
[0114] Examples of the epoxy group-containing organoalkoxysilane include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane.
[0115] The ratio of the alkoxysilane having an organic group containing an amino group to the alkoxysilane having an organic group containing an epoxy group is preferably in the range of (1:1.5) to (1:5), and particularly preferably in the range of (1:2) to (1:4) in terms of molar ratio. This component can be easily synthesized by mixing the alkoxysilane having an organic group containing an amino group and the alkoxysilane having an organic group containing an epoxy group as described above and reacting them at room temperature or under heating.
[0116] In particular, the composition of the present invention preferably contains an alkoxysilane having an amino group-containing organic group and an alkoxysilane having an epoxy group-containing organic group, which are cyclized by an alcohol exchange reaction when an alkoxysilane having an amino group-containing organic group is reacted with an alkoxysilane having an epoxy group-containing organic group by the method described in Japanese Patent Application Laid-Open No. 10-195085, and particularly preferably contains a silane having the general formula:
[0117] [Chemical formula 1]
[0118]
[0119] {In the formula, R 1 is an alkyl group, an alkenyl group or an alkoxy group, R 2 are the same or different and are selected from the general formula:
[0120] [Chemical formula 2]
[0121]
[0122] (Where R 4 is alkylene or alkyleneoxyalkylene, R 5 is a monovalent hydrocarbon group, R 6 is an alkyl group, R 7 is an alkylene group, R 8 is an alkyl, alkenyl or acyl group, and a is 0, 1 or 2. )
[0123] The group consisting of the groups shown in the figure, R 3 are the same or different hydrogen atoms or alkyl groups.
[0124] Examples of such a silazolyl derivative include a silazolyl derivative having a silicon atom-bonded alkoxy group or a silicon atom-bonded alkenyl group in one molecule and represented by the following structure.
[0125] [Chemical formula 3]
[0126]
[0127] (In the formula, Rc is a group selected from methoxy, ethoxy, vinyl, allyl and hexenyl.)
[0128] In the present invention, a silazoline derivative represented by the following structural formula may also be used as a thickener.
[0129] [Chemical formula 4]
[0130]
[0131] R in the formula 1 are the same or different hydrogen atoms or alkyl groups, in particular, as R1 , preferably a hydrogen atom or a methyl group. 2 is selected from the group consisting of a hydrogen atom, an alkyl group, and a group of the general formula: -R 4 -Si(OR 5 ) x R 6 (3-x) The same or different groups in the group consisting of the alkoxysilyl-containing organic groups shown, but R 2 At least one of R is an organic group containing an alkoxysilyl group. 2 The alkyl group of R includes, for example, a methyl group. 2 In the organic group containing an alkoxysilyl group, R 4 is a divalent organic group, and examples thereof include alkylene or alkyleneoxyalkylene, and particularly preferably ethylene, propylene, butylene, methyleneoxypropylene, and methyleneoxypentylene. 5 is an alkyl group having 1 to 10 carbon atoms, preferably a methyl group or an ethyl group. 6 is a substituted or unsubstituted monovalent hydrocarbon group, preferably a methyl group. In the formula, x is 1, 2 or 3, preferably 3.
[0132] As such R 2 Examples of the alkoxysilyl-containing organic group include the following groups.
[0133] -(CH2)2Si(OCH3)2(CH2)2Si(OCH3)2CH3
[0134] -(CH2)3Si(OC2H5)2(CH2)3Si(OC2H5)(CH3)2
[0135] -CH2O(CH2)3Si(OCH3)3
[0136] -CH2O(CH2)3Si(OC2H5)3
[0137] -CH2O(CH2)3Si(OCH3)2CH3
[0138] -CH2O(CH2)3Si(OC2H5)2CH3
[0139] -CH2OCH2Si(OCH3)2CH2OCH2Si(OCH3)(CH3)2
[0140] R in the above formula 3is at least one group selected from the group consisting of a substituted or unsubstituted monovalent hydrocarbon group, an alkoxy group having 1 to 10 carbon atoms, a glycidyloxyalkyl group, an ethylene oxide alkyl group, and an acyloxyalkyl group, and R 3 As a monovalent hydrocarbon group, an alkyl group such as a methyl group can be exemplified. 3 The alkoxy group of R includes methoxy, ethoxy, and propoxy. 3 The glycidyloxyalkyl group of R is exemplified by 3-glycidyloxypropyl. 3 The oxiranyl alkyl group of R includes 4-oxiranylbutyl and 8-oxiranyloctyl. 3 Examples of the acyloxyalkyl group include acetoxypropyl and 3-methacryloyloxypropyl. 3 , preferably an alkyl group, an alkenyl group, or an alkoxy group, more preferably an alkyl group or an alkenyl group, and particularly preferably a group selected from a methyl group, a vinyl group, an allyl group, and a hexenyl group.
[0141] The amount of component (H) used is not particularly limited, but is preferably in the range of 0.1 to 1.0 mass %, more preferably 0.2 to 1.0 mass %, based on the entire composition, from the viewpoint of improving adhesion to dielectric layers and the like.
[0142] [Use of solvent]
[0143] The electrode layer forming curable organopolysiloxane composition of the present invention can be designed to have heating melting property or fluidity at room temperature, and does not need to use solvent in essence. It can be designed to be solvent-free, and no fluorine-based solvent, organic solvent, etc. remain in the film obtained by curing, and it has the advantages of being able to eliminate the problem of environmental load and the influence of solvent on electronic equipment. Among them, for the composition of the present invention, it does not prevent the use of organic solvents that are inevitably mixed into its raw material components, etc., and a small amount of organic solvents are considered from the perspective of handling. Specifically, the composition of the present invention can be a low-solvent type to solvent-free type composition containing 5 mass parts or less, preferably 1 mass part or less, and more preferably an organic solvent below the detection limit relative to the sum (100 mass parts) of the above-mentioned (A), (B), and (E) components. It should be noted that as an example of a solvent, one or more organic solvents selected from (S1) organic polar solvents, (S2) low molecular weight siloxane solvents, and (S3) halogen solvents or mixed solvents thereof can be shown, and in particular, solvents with a boiling point of 80°C or more and less than 200°C can be shown.
[0144] The composition according to the present invention is most preferably in the form of a solvent-free composition in which the content of the organic solvent is 1 part by mass or less or below the detection limit and substantially contains no organic solvent.
[0145] Furthermore, in the present composition, as long as the purpose of the present invention is not impaired, other optional components may also be included: heat resistant agents such as iron oxide (red iron oxide), cerium oxide, dimethylsilanol cerium, fatty acid cerium salt, cerium hydroxide, zirconium compounds, etc.; dyes, other pigments other than white, flame retardants, aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, phosphazene, etc., ion scavengers / pH adjusters such as hydrotalcite, bismuth oxide, yttrium oxide, etc., flame retardants such as aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, phosphazene, etc., hindered phenol compounds, Antioxidants such as hindered amine compounds and sulfide compounds, soft magnetic particles such as pure iron, silicon steel, iron-cobalt alloy, iron-nickel alloy, iron-chromium alloy, iron-aluminum alloy, carbonyl iron, stainless steel, or composite materials containing one or more of these, inorganic flame retardants (such as hydrated metal compounds such as aluminum hydroxide), halogen flame retardants, phosphorus flame retardants, organic metal salt flame retardants, silicone oil, silicone rubber, polyisoprene, 1,2-polybutadiene, 1,4-polybutadiene and other polybutadiene, styrene-butadiene rubber, acrylonitrile-butadiene rubber, Carboxyl-terminated butadiene acrylonitrile rubber, polychloroprene, poly(propylene oxide), poly(oxytetramethylene glycol), polyolefin glycol, poly-ε-caprolactone and other thermoplastic elastomers, polysulfide rubber, fluororubber and other stress reducing agents, barium titanate (BaTiO3), strontium titanate (SrTiO3), lead zirconate titanate (Pb(Zr,Ti)O3, also known as PZT), aluminum oxide (Al2O3, also known as aluminum oxide), zirconium oxide (ZrO2, also known as zirconium dioxide), magnesium oxide (MgO, also known as magnesium oxide), silicon dioxide (SiO2 , alias: silicon oxide), titanium dioxide (TiO2, alias: titanium oxide), aluminum nitride (AlN), silicon nitride (Si3N4), silicon carbide (SiC), barium calcium zirconate titanate (alias: BCTZ), polyvinylidene fluoride and other dielectric ceramics, copper chloride, cuprous iodide, copper acetate, cerium stearate and other metal salt stabilizers; hindered amine series, hindered phenol series, sulfur-containing compound series, acrylate series, phosphorus series organic compound and other antioxidants or heat stabilizers; benzophenone series, salicylate series, benzotriazole series and other ultraviolet absorbers or weathering agents, light stabilizers, etc. In addition, when the present composition has heat-melting properties, an organic wax may be blended to improve the heat-melting properties.
[0146] [Use of the present composition: Formation of electrode layer]
[0147] The present composition has fluidity at room temperature or by heating and melting, can be evenly applied to the desired part, and can form an electrode layer through a curing process, so it can be used without restriction in a solvent-free process and an electrode printing process for the purpose of reducing environmental load and improving the performance of actuators, etc. Further, the present composition is excellent in formability, gap filling and adhesion, and in addition to the heat resistance, durability and adhesion of the obtained electrode layer, the temperature dependence of the viscoelastic properties, especially at high temperatures, is small, so especially in the case of forming an electrode layer formed by using the present composition on a dielectric elastomer sheet, its tracking and shape retention are significantly excellent, even in the case of using a transducer that is based on a high degree of physical displacement as an actuator, it is not easy to produce problems of peeling and defects of the electrode layer, and it has sufficient viscoelastic properties for practical use.
[0148] The present composition has curing reactivity, and is applied to a portion where an electrode layer is to be formed, and a curing reaction is carried out during or after the application, thereby forming an electrode layer composed of a cured product. When components (C) and (D) are used, the curing reaction is a hydrosilylation reaction, and depending on the type of component (D), a heat curing reaction, a curing reaction using high-energy radiation, or a combination thereof can be selected.
[0149] The temperature of the heat curing reaction is not particularly limited, but is preferably 50°C or more and 200°C or less, more preferably 60°C or more and 200°C or less, and further preferably 80°C or more and 180°C or less. In addition, the time taken for the curing reaction is usually 1 second or more and 3 hours or less. In general, a cured product can be obtained by keeping it in the range of 90°C to 180°C for 10 seconds to 30 minutes. It should be noted that, as described above, in the case of selecting thermoplastic resin particles containing platinum hydrosilylation reaction catalysts using thermoplastic resins having specific softening points or glass transition points as component (D), the curing reaction does not proceed at a temperature below the softening point or glass transition point of the thermoplastic resin (wall material), and the curing reaction is rapidly carried out by heating at a temperature above it, so it has the advantage of being easy to control the temperature of the curing reaction.
[0150] When at least a part of component (D) is the above-mentioned high-energy ray-activated catalyst, the present composition performs a curing reaction triggered by irradiation with high-energy rays. As active energy rays that can be used for the curing reaction, ultraviolet rays, electron beams, and radiation, etc. can be listed, but ultraviolet rays are preferred in terms of practicality. In the case of using ultraviolet rays for the curing reaction, it is preferred to add a catalyst for the hydrosilylation reaction that has high activity relative to the ultraviolet rays used, such as bis(2,4-pentanedionate) platinum complex and (methylcyclopentadienyl) trimethylplatinum complex. As the ultraviolet light generating source, high-pressure mercury lamps, medium-pressure mercury lamps, Xe-Hg lamps, and deep ultraviolet lamps (Deep UV Lamp) are preferred, and the irradiation amount at this time is preferably 100 to 8,000 mJ / cm 2 .
[0151] The thickness and shape of the electrode layer can be appropriately designed as desired. When having the above-mentioned volume resistance value (conductivity), it can be in the form of a thin film, and the average thickness thereof is preferably in the range of 1 to 100 μm.
[0152] The electrode layer obtained by the curing reaction has a low temperature dependence of the viscoelastic properties, especially at high temperatures, and since it is a cured product, the mechanical strength of the electrode layer itself, the adhesion to the substrate, and the followability tend to be further improved. By using the electrode layer as the cured product, it has the advantage of being particularly excellent in followability and shape retention. In addition, since the curing reaction is easy to control, a flexible process design including a solvent-free process can be performed.
[0153] [Uses of the present composition: laminate and dielectric layer]
[0154] The electrode layer obtained using this composition can be used for desired semiconductor components and electronic components, etc., can be used for electronic components such as semiconductor chips, electronic circuits, semiconductor (including optical semiconductor) devices, etc. without particular restrictions, and can form a laminate having this electrode layer. In particular, the electrode layer obtained using this composition is excellent in temperature dependence of viscoelastic properties in addition to heat resistance, durability, and adhesion, so in particular, in the case of forming an electrode layer using this composition on a dielectric elastomer sheet, its followability and shape retention are significantly excellent, even in the case of a transducer that is premised on a high degree of physical displacement as an actuator, it is also possible to form a laminate that is not prone to the peeling of the electrode layer, the problem of defects. It should be noted that the type of dielectric elastomer sheet is not particularly limited, but from the perspective of its mechanical strength, heat resistance, flexibility, and electrochemical characteristics, it is particularly preferred as a dielectric layer of an organopolysiloxane cured product film.
[0155] Specifically, the laminate having an electrode layer obtained using the present composition preferably has a structure in which (L2) an electrode layer composed of the electrode layer-forming curable organopolysiloxane composition is laminated on at least one surface of (L1) a cured organopolysiloxane film as a dielectric layer.
[0156] Cured organopolysiloxanes having a polysiloxane skeleton have excellent transparency, electrical insulation, heat resistance, cold resistance, etc., and can be improved in electrical activity by introducing high dielectric functional groups such as fluoroalkyl groups as desired, and can be easily processed into a film or sheet shape. Therefore, they are particularly suitable for use as dielectric layers as adhesive films for various electrical / electronic equipment and electroactive films for transducer devices such as actuators.
[0157] The curing mechanism of the organopolysiloxane cured film is classified into hydrosilylation reaction curing type, condensation reaction curing type, peroxide curing type, etc. It is rapidly cured by being left at room temperature or heated, and does not produce by-products. Therefore, it is particularly preferred to use an organopolysiloxane cured film of a curable organopolysiloxane composition of the hydrosilylation reaction curing type.
[0158] The organopolysiloxane cured film as the dielectric layer is in the form of a thin film, and the average thickness of the film is preferably in the range of 1 to 200 μm, the average thickness is preferably in the range of 1 to 150 μm, and the average thickness is more preferably in the range of 1 to 100 μm. Here, the average thickness of the film is the average value of the thickness at the center of the film. Preferably, the organopolysiloxane cured film is uniform and flat, and in the width direction of the film, it is more preferred that the difference between the thickness at the end and the thickness at the center is within 5.0%, and the average value of the thickness at the center of the film is in the range of 5 to 200 μm.
[0159] Similarly, when the number of internal defects of the cured organopolysiloxane film as the dielectric layer is measured using an optical cell within a unit area of 15 mm×15 mm at an optional location, the number of internal defects is in the range of 0 to 20, preferably in the range of 0 to 15. If the number of internal defects exceeds the upper limit described above, dielectric breakdown may occur easily when a high voltage is applied to the film, and the dielectric breakdown strength of the entire film may be significantly reduced.
[0160] The dielectric breakdown strength of the organopolysiloxane cured film as the dielectric layer measured at room temperature is in the range of 56V / μm to 200V / μm, more preferably in the range of 58V / μm to 100V / μm. In addition, the organopolysiloxane cured film of the present invention can also be easily designed to have a relative dielectric constant of 3 or more, 4 or more, 5 or more, or 6 or more at 1kHz and 25°C by optionally using an amount of a high dielectric functional group such as a fluoroalkyl group and a high dielectric filler.
[0161] When the organopolysiloxane cured film as the dielectric layer is heat-molded into a sheet shape having a thickness of 2.0 mm, it can be designed to have the following mechanical properties measured in accordance with JIS K 6249.
[0162] (1) The Young's modulus (MPa) can be 10 MPa or less at room temperature, and a particularly preferred range is 0.1 to 2.5 MPa.
[0163] (2) The tear strength (N / mm) can be 1 N / mm or more at room temperature, and a particularly preferred range is 2 N / mm or more.
[0164] (3) The tensile strength (MPa) can be 1 MPa or more at room temperature, and a particularly preferred range is 2 MPa or more.
[0165] (4) The elongation (%) at break can be 50% or more, and a particularly preferred range is 100 to 1000%.
[0166] When the organopolysiloxane cured film as a dielectric layer is used as an electronic material such as a touch panel, an electronic component for a display device, and particularly a transducer material such as a sensor, the shear storage modulus at 23° C. is preferably 10 3 ~10 5 The range of Pa is more preferably 1.0×10 3 ~5.0×10 4 The range of Pa.
[0167] As described above, the average thickness of the organopolysiloxane cured film as the dielectric layer is within the range of 1 to 200 μm per sheet, but a plurality of films may be stacked to form a laminated film having a thickness exceeding 200 μm for the purpose of forming a dielectric layer.
[0168] [Formation of Laminated Body]
[0169] The above-mentioned laminated body can be preferably obtained by, for example, a method for producing a laminated body having the following steps: Step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film-like shape, thereby obtaining an organopolysiloxane cured film as a dielectric layer; Step II: a step of applying the above-mentioned electrode layer-forming curable organopolysiloxane composition on the organopolysiloxane cured film or its precursor involved in step I simultaneously with step I or after step I, to form an electrode layer. It should be noted that the method of applying the electrode layer-forming curable organopolysiloxane composition in step II is not particularly limited, and a well-known coating method such as dispensing can be appropriately used according to the properties of the composition and the desired shape of the electrode layer. Furthermore, the formation of the electrode layer includes: optionally having a heating and melting step, and forming the electrode layer as a cured product by utilizing the curing reaction of the composition after application.
[0170] In particular, when the curing reaction involved in the formation of the dielectric layer involved in the above-mentioned step I and the formation of the electrode layer involved in the step II are curing reactions accompanied by the formation of a cured product, and when these curing reactions both include a hydrosilylation reaction, by selecting a composition having different ratios of hydrogen atoms bonded to silicon atoms (hereinafter sometimes abbreviated as "SiH / Vi ratio") in the organohydrogenpolysiloxane component relative to 1 mol of the total amount of carbon-carbon double bonds in the curable organopolysiloxane composition involved in the formation of the dielectric layer or the curable organopolysiloxane composition for forming the electrode layer, it is sometimes possible to provide a structure in which two layers are chemically bonded by a hydrosilylation reaction at the interface between the dielectric layer and the electrode layer, thereby further improving the followability and shape retention of the electrode layer involved in the present invention to the dielectric layer, and suppressing the peeling and defect generation of the electrode layer.
[0171] As an example, for the electrode layer-forming curable organopolysiloxane composition according to the present invention, the SiH / Vi ratio ([SiH / Vi] Elec ) is 0.2 mol or more and 1.5 mol or less, preferably 0.3 mol or more and 1.2 mol or less, and more preferably 0.3 mol or more and 1.0 mol or less. For the curable organopolysiloxane composition for forming the dielectric layer, its SiH / Vi ratio ([SiH / Vi] DEAP ), particularly preferably [SiH / Vi] Elec / [SiH / Vi] DEAPThe value is in the range of 0.20-0.90, 0.33-0.85, 0.50-0.75, 0.58-0.67. That is, it is particularly preferred that the composition forming the dielectric layer is a combination with a certain degree of excess SiH. This is because, in the case where these curable organopolysiloxane compositions are cured by hydrosilylation reaction, in the interface, the excess SiH groups present on the dielectric layer side are easily hydrosilylated with the curable reactive groups containing carbon-carbon double bonds in the electrode layer forming curable organopolysiloxane composition in the interface of the two layers, and it is easy to provide a two-layer chemically bonded structure. This manufacturing method is particularly useful as a method for forming an electrode layer in a transducer component, and can easily provide a dielectric layer and an electrode layer firmly bonded in industry, and is not easy to produce problems of peeling or defects accompanied by insufficient bonding strength and tracking properties of the laminated body, electronic parts or display device.
[0172] The laminate of the organopolysiloxane cured film of the present invention is useful as an electronic material, a component for a display device, or a component for a transducer (including a sensor, a speaker, an actuator, and a generator), and can be used as an electroactive film (including a high dielectric film) with an electrode layer, preferably as a component of an electronic component or a display device. Further, as described above, the electroactive film with high dielectric breakdown strength is preferably a transducer component of an actuator, etc. in the form of a single layer or a laminated film, and the electrode layer of the present invention has the following characteristics: it can be formed on the dielectric layer without special restrictions even in a solvent-free process or an electrode printing process accompanied by heating and melting, and the followability and shape retention of the organopolysiloxane cured film as a dielectric layer are significantly excellent, and it is not easy to produce the problem of peeling and defects of the electrode layer, so it is particularly useful for the actuator application started at a high voltage.
[0173] It should be noted that the laminate of the cured organopolysiloxane film of the present invention preferably has a whole or partial structure, wherein the whole or partial structure has an electrode layer on one side of the dielectric layer, these layers are alternately stacked, and the electrode layer is arranged on the outside. Furthermore, the laminate of the present invention may have a pressure-sensitive adhesive layer used for the purpose of being arranged in the transducer, and a non-silicone thermoplastic resin layer that may optionally have a release surface, in addition to the electrode layer of the present invention and the single-layer or multi-layer dielectric layer.
[0174] [Example]
[0175] The present invention will be described below with reference to Examples, but the present invention is not limited to these Examples. The following compounds were used in the Examples shown below.
[0176] Component (a1-1): dimethylsiloxane polymer terminated at both ends with vinyldimethylsiloxy groups (vinyl content: 0.09% by mass, siloxane polymerization degree: 835)
[0177] Component (a1-2): dimethylsiloxane polymer terminated at both ends with vinyldimethylsiloxy groups (vinyl content: 1.53% by mass, siloxane polymerization degree: 45)
[0178] Component (a1-3): dimethylsiloxane polymer terminated at both ends with vinyldimethylsiloxy groups (vinyl content: 0.14% by mass, siloxane polymerization degree: 537)
[0179] Component (a1-4): dimethylsiloxane polymer terminated at both ends with vinyldimethylsiloxy groups (vinyl content: 0.24% by mass, siloxane polymerization degree: 300)
[0180] Component (a2): a copolymer of 3,3,3-trifluoropropylmethyl and dimethylsiloxane terminated at both ends with vinyldimethylsiloxy groups (vinyl content: 0.26% by mass, siloxane polymerization degree: 193)
[0181] Component (b1): trimethylsilyl units (M) and vinyldimethylsilyl units ( Vi M) and tetrafunctional siloxy units (Q, SiO 4 / 2 ) units (vinyl content: 1.9 mass %, weight average molecular weight in terms of polystyrene measured by GPC (gel permeation chromatography) using tetrahydrofuran as solvent: Mw = 2.4 × 10 4 Mw=2.4×10 4 )
[0182] Component (b2): trimethylsiloxy units (M) and tetrafunctional siloxane units (Q, SiO 4 / 2 ) units (using toluene as solvent, the weight average molecular weight in terms of polystyrene measured by GPC is Mw=6.4×10 3 )
[0183] Component (bx): trimethylsiloxy unit (M) and tetrafunctional siloxane unit (Q, SiO 4 / 2 ) units (using toluene as solvent, the weight average molecular weight in terms of polystyrene measured by GPC is Mw=3.4×10 3 )
[0184] Component (f1): Fumed silica treated with hexamethyldisilazane and dimethylsiloxy-methylvinylsiloxane-siloxane copolymer terminated with hydroxydimethylsiloxy groups at both ends (CAB-O-SIL MS-75)
[0185] Component (f2): fumed silica treated with hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane (product name before treatment: AEROSIL 200, BET specific surface area 200 m2 / g)
[0186] Component (f3): fumed silica treated with hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane (product name before treatment: AEROSIL 50, BET specific surface area 50 m2 / g)
[0187] Component (c1): dimethylsiloxane polymer terminated at both ends by dimethylhydrogensiloxy groups (silicon-bound water content: 0.123 mass %)
[0188] Component (c2): a dimethylsiloxy-methylhydrosiloxy-siloxane copolymer terminated at both ends by trimethylsiloxy groups (silicon-bound water content: 0.71% by mass)
[0189] Component (c3): dimethylsiloxane polymer terminated at both ends by dimethylhydrogensiloxy groups (silicon-bound water content: 0.015 mass %)
[0190] Component (c4): a dimethylsiloxane / 3,3,3-trifluoropropylmethylsiloxane / methylhydrogensiloxane copolymer (content of silicon-bonded hydrogen: about 0.23% by mass) terminated at both ends by trimethylsiloxy groups
[0191] Component (c5): a dimethylsiloxane / 3,3,3-trifluoropropylmethylsiloxane copolymer having both ends blocked with dimethylhydrogensiloxy groups (content of silicon-bonded hydrogen: about 0.014 mass %)
[0192] Component (d1): Masterbatch comprising thermoplastic resin microparticles containing a platinum catalyst (*) Masterbatch comprising microparticles containing a platinum catalyst prepared by the method described in the following Reference Example (the platinum metal concentration is 0.16% by mass)
[0193] Component (d2): a solution of a dimethylsiloxane polymer capped with vinyldimethylsiloxy groups at both ends of a platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex (about 0.6% by mass in terms of platinum concentration)
[0194] [Reference Example (Preparation of Masterbatch Containing Thermoplastic Resin Microparticles Containing Platinum Catalyst)]
[0195] Into a flask equipped with a stirrer, 900 g of a bisphenol A-type thermoplastic polycarbonate resin (glass transition temperature (Tg) 145°C; wall material), 500 g of toluene, and 4600 g of dichloromethane were added and uniformly mixed. 44.4 g of a divinyltetramethyldisiloxane solution of a platinum (0-valent) divinyltetramethyldisiloxane complex (platinum metal concentration of 5% by mass) was added and mixed to obtain a uniform solution. The solution was sprayed / dried using a spray dryer with nitrogen as a hot air flow to obtain 450 g of spherical thermoplastic resin particles containing a platinum catalyst (average particle size of 1.1 μm).
[0196] Next, 40 parts by mass of the thermoplastic resin particles containing the platinum catalyst were mixed with 60 parts by mass of dimethylpolysiloxane having a viscosity of 350 mPa·s and a vinyl content of 0.47% and having both ends of the molecular chain capped with dimethylvinylsiloxane groups, to prepare a master batch containing particles containing the platinum catalyst. The concentration of platinum metal in the master batch was 0.16% by mass.
[0197] <Conductive filler>
[0198] Component (e1): Carbon filler (PRINTEX(TM) XE2 B)
[0199] Component (e2): single-walled carbon nanotube (SWCNT, 10% by mass of a dimethylsiloxane polymer terminated with trimethylsiloxy groups at both ends, TUBALL(TM) MATRIX 601)
[0200] Component (e3): Acetylene black (manufactured by Denka Co., Ltd., 100% pressed product)
[0201] <Hydrosilylation Reaction Inhibitor>
[0202] Component (g1): 1-ethynylcyclohexanol
[0203] Component (g2): 1,3,5,7-Tetramethyl-1,3,5,7-tetravinyl-cyclotetrasiloxane
[0204] [Examples 1 to 4 and Comparative Examples 1 to 3]
[0205] Table 1 shows the composition of each experimental example of the embodiment and the comparative example. The numerical value corresponding to each component is mass %, and the sum is 100 mass %. In addition, in the following examples, the silicon atom-bonded hydrogen atom (Si-H) of the component (c) is used in an amount ranging from 0.35 to 1.0 mole per 1 mole of vinyl (unsaturated hydrocarbon group, the same below) in the composition. Further, the physical properties before or after curing measured by the following method are shown in Tables 1 and 2.
[0206] [Examples 5 to 18 and Comparative Examples 4 to 5]
[0207] Tables 2 and 3 show the compositions of Examples 5 to 18 and Comparative Examples 4 to 5, respectively. The values corresponding to each component are in mass %, and the sum is 100 mass %. The silicon atom-bonded hydrogen atom (Si-H) of component (c) is used in an amount of 0.87 to 0.93 moles per 1 mole of vinyl in the composition. Furthermore, the physical properties before or after curing measured by the following method are shown in Tables 2 and 3.
[0208] [Volume fraction of each component]
[0209] In the present invention, the true density of each component at 25°C in the composition is defined as follows, and the volume fraction is calculated: Component (b) is 1.23 g / cc, component (f) is 2.20 g / cc, component (e1) is 2.00 g / cc, single-walled carbon nanotubes (SWCNT) in component (e2) is 1.58 g / cc, and other components are 0.98 g / cc.
[0210] [Mw of component (b)]
[0211] When the component (b) is mixed and used, Mw is calculated as follows.
[0212]
[0213] In the above formula (1), Mwk and wfk are the Mw of the kth component (b) and the weight fraction of the kth component (b), respectively.
[0214] [Preparation of samples of Examples 1 to 4 and Comparative Examples 1 to 3]
[0215] After weighing ingredients other than component (d1) into a 300cc wide-mouth glass sample bottle, heat in an oven at 125°C for about 30 minutes. Then, on a hot plate heated to 180°C, mix with an electric stirrer for more than 30 minutes while scraping off the attached materials on the wall of the sample bottle. After cooling, add component (d1) and mix with an electric stirrer for more than 30 minutes on a hot plate heated to 120°C while scraping off. Then, transfer the mixture to a 100cc HDPE container and heat in an oven at 110°C for more than 10 minutes. Take it out of the oven and mix it at 2000RPM for more than 4 minutes using a Thinky mixer (ARE-310).
[0216] [Preparation of samples of Examples 5 to 18 and Comparative Examples 4 to 6]
[0217] Except for Comparative Example 6, components (a), (b1), (f1) and component (e) were placed in a 100cc HDPE container and mixed at 2000RPM for more than 4 minutes using a Thinky mixer (ARE-310). After confirming the uniformity in appearance, components (c) and (g) were added and mixed under the same conditions. After cooling, component (d2) was finally added and mixed at 1200RPM for more than 2 minutes using a Thinky mixer (ARV-310LED).
[0218] Comparative Example 6 was carried out in the same manner as above except that the components other than the component (d2) were mixed in the same manner.
[0219] [Preparation of samples of Examples 1 to 4 and Comparative Examples 1 to 3]
[0220] [Viscoelasticity measurement of Examples 1 to 4 and Comparative Examples 1 to 3]
[0221] The measurement was performed using a viscoelasticity measuring device (manufactured by Anton Paar, model MCR302). On the lower plate of a Peltier element temperature control system heated to 120°C, an appropriate amount of each curable composition was placed, and the sample was placed to a thickness of about 1.5 mm using a parallel plate with a diameter of 15 mm. Under the conditions of a frequency of 1 Hz and a deformation of 0.1%, after cooling to -20°C at 3°C per minute, the temperature was raised to 150°C and maintained for 180 minutes to solidify it. Furthermore, cooling and heating were repeated again. The storage modulus (G') and loss tangent (tanδ) before and after curing (first heating and second heating) at 25°C and 110°C are shown in Table 1.
[0222] [Viscoelasticity measurement of Examples 5 to 18 and Comparative Examples 4 to 6]
[0223] The viscoelasticity measuring device (manufactured by Anton Paar, model MCR302) was used for the measurement. On the lower plate with a Peltier element temperature control system, a parallel plate with a diameter of 15 mm was used to place the sample at 25°C to a thickness of about 0.5 mm. Under the conditions of a frequency of 1 Hz and a deformation of 0.1%, the temperature was raised to 110°C at 3°C per minute and maintained for more than 60 minutes to cure. The storage modulus (G') and loss tangent (tanδ) after curing from the start of the temperature rise to 45 minutes are shown in Tables 2 to 5.
[0224] [Preparation of Cured Products of Examples 1 to 4 and Comparative Examples 1 to 3 and 6]
[0225] In other than Comparative Example 6, a mold of 50 mm long × 50 mm wide × 2 mm thick is placed on a metal plate, and a PTFE film (150 microns thick) is set thereon. An appropriate amount of each composition is placed on the PTFE film and heated in an oven at 120°C for more than 30 minutes. Take it out of the oven, set a PTFE film on the composition, and further clamp it with a metal plate. After that, pre-cure at 150°C for 15 minutes, and then post-cure (postcure) for 45 minutes in an oven at 150°C to obtain a sheet-like cured product. Regarding Comparative Example 6, a mold of 50 mm long × 30 mm wide × 6 mm thick is used, and it is not subjected to heat treatment but is clamped with a metal plate in the same manner, pre-cured at 120°C for 15 minutes, and further post-cured in an oven at 120°C for 45 minutes to obtain a block-like cured product.
[0226] [Measurement of Volume Resistivity (VR) of Cured Materials of Examples 1 to 4 and Comparative Examples 1 to 3]
[0227] The analysis was performed using LORESTA-GP MCP-T610 (PSP probe, manufactured by Mitsubishi Chemical Analytical Tech Co., Ltd.) at about 25° C. The calculation was performed using a correction factor according to the shape of the sample.
[0228] [VR Measurement of Examples 5 to 18 and Comparative Examples 4 and 5]
[0229] <Example electrode coating on substrate PET sheet>
[0230] Each composition was diluted with the silicone solvent OS-20 (DOW PERFORMANCE SILICONE) at the concentration described in Table 2, and an 80-micron-thick NITOFLON spacer (manufactured by Nitto Denko Corporation) was set on a 200-micron-thick PET film, and rod coating was performed (area of about 70 mm×100 mm). After coating, the solvent was distilled off in a vacuum at 60°C for about half a day. Thereafter, a PET-based release liner film was covered on the coated composition and pressed with a 2KG roller. The release liner film was peeled off and heated in an oven at 120°C for 1 hour to form an electrode layer of about 10 to 30 microns thick. The VR values measured by the above-described method are shown in Tables 2 to 5.
[0231] [VR Measurement during Biaxial Stretching of Example 17 and Comparative Example 6]
[0232] <Base DEAP Sheet>
[0233] The liquid curable organopolysiloxane composition was prepared by mixing and preparing the above-mentioned component (a2) at 68.34 mass%, component (c4) at 5.06 mass%, component (c5) at 5.06 mass%, component (d2) at 0.10 mass%, component (f2) at 18.69 mass%, component (f3) at 2.46 mass%, and component (g2) at 0.28 mass%. At this time, the silicon-bonded hydrogen atoms (Si—H) of the component (d) per 1 mol of the unsaturated hydrocarbon groups in the composition were as follows: (SiH / unsaturated hydrocarbon group): DEAP The hardness of the organopolysiloxane cured product obtained by curing at 110° C. for 1 hour was Shore A 37. The sheet used had a thickness of about 100 μm.
[0234] <Example Electrode Coating on DEAP Sheet Substrate>
[0235] Each composition was diluted with the silicone solvent OS-20 (DOW PERFORMANCE SILICONE) at the concentration described in Table 4 or 5, and an electrode layer with a diameter of 30 mm and a thickness of about 10 to 25 μm was formed using a spray gun under the same conditions as the VR measurement of Examples 5 to 18.
[0236] <Biaxial Stretching of Electrode Layer>
[0237] The initial radius was set to 1, and the stretch ratio (λ) was increased to 1.12, 1.22, 1.32, and 1.41, and then decreased conversely. After reaching each λ, the VR values measured by the above-described method were shown in Table 6 after being left for more than 1 minute.
[0238] [Table 1]
[0239]
[0240] [Table 2]
[0241]
[0242] [Table 3]
[0243]
[0244] [Table 4]
[0245]
[0246] [Table 5]
[0247]
[0248] [Table 6]
[0249]
[0250] *Since the VR value changes greatly during biaxial stretching, it was not measured.
[0251] [Summarize]
[0252] As described above, in Examples 1 to 4, since the component (b) does not exceed the prescribed amount, the temperature dependence of the viscoelasticity of the cured product is small. On the other hand, in Comparative Examples 1 to 3, since the amount of the component (b) exceeds the prescribed amount, the temperature dependence of the viscoelasticity of the cured product becomes large. In particular, in the electrode-forming curable composition of the present invention, if the content of the component (b) exceeds the prescribed amount, in practice, when the operating temperature of the device changes up and down, the viscoelasticity of the electrode layer is prone to change depending on the temperature, and the performance of the electrode layer deviates or becomes unstable, which is very worrying. It should be noted that in Example 2, the Mw of the component (bx) is small, and even if it is formulated in a manner of 0.5 in volume fraction, the temperature dependence of the viscoelasticity is small. That is, by selectively utilizing a substance with a small Mw value as the component (bx), even if the organic polysiloxane resin component is formulated in a prescribed amount or more, a composition having sufficient performance in practice and a small temperature dependence of the viscoelasticity of the electrode layer obtained by curing can be designed.
[0253] It can be seen from Examples 5 to 18 that by heat curing under the condition that component (b) does not exceed the specified amount, it can be adjusted to a moderate viscoelasticity. In any embodiment, a specified amount of component (e) as conductive particles, especially component (e2) as single-walled carbon nanotubes (SWCNT), is formulated. Compared with Comparative Examples 4 and 5, in any embodiment, the volume fraction of (e2) is above the specified amount. Therefore, the VR after curing is maintained low. In addition, it can be seen that when biaxial stretching is used in Example 17, the value of VR hardly changes. On the other hand, in Comparative Example 6 containing only component (e3), the value of VR changes greatly during biaxial stretching, so involving these embodiments, in the optimized composition involved in the present invention, when the electrode layer obtained by curing it is used as an electrode for various transducer uses represented by actuators, its performance is expected to be high.
Claims
1. An electrode layer-forming curable organopolysiloxane composition comprising: (A) a chain organopolysiloxane having curing reactive functional groups containing carbon-carbon double bonds at least at both ends of the molecular chain; (B) an organopolysiloxane resin having a weight average molecular weight of 5,000 or more in terms of standard polystyrene, comprising R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane units (Q units) shown; and (E) conductive particles, in, The content of the component (B) in the composition is less than 45% by mass based on the entire composition.
2. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The conductive fine particles are fine particles containing at least one conductive carbon selected from the group consisting of carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor grown carbon (VGCF).
3. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The conductive fine particles are fine particles including single-walled carbon nanotubes (SWCNTs).
4. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The volume fraction of the conductive fine particles relative to the entire composition is in the range of 0.003 to 0.50, and the volume resistivity of the electrode layer obtained using the present composition is 10 3 Ω·cm or less.
5. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The present invention comprises: component (A), component (B) and optionally (BX) an organopolysiloxane resin, wherein the organopolysiloxane resin has a molecular weight of less than 5000 in terms of standard polystyrene and contains R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane units (Q units) shown, The content of the components (A), (B) and (BX) in the entire composition is in the range of 50 to 95% by mass, and the mass ratio of the components (A) to (B) is in the range of 100:0 to 50:
50.
6. The electrode layer-forming curable organopolysiloxane composition according to claim 1, It comprises: (A1) a linear organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain; (B) an organopolysiloxane resin having a weight average molecular weight of 5,000 or more in terms of standard polystyrene, comprising R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane units (Q units) shown; (C) the silicon-bonded hydrogen atoms in the present component are present in an amount of 0.1 to 1.5 mol per 1 mol of the total amount of carbon-carbon double bonds in the organohydrogenpolysiloxane composition having at least two silicon-bonded hydrogen atoms in the molecule; (D) an effective amount of a catalyst for a hydrosilylation reaction; (E1) conductive particles comprising single-walled carbon nanotubes (SWCNTs); as well as (F) reinforcing fillers, The volume fraction of the single-walled carbon nanotube (SWCNT) relative to the entire composition is in the range of 0.0015 to 0.
25.
7. The electrode layer-forming curable organopolysiloxane composition according to claim 6, wherein At least a portion of component (C) is (C1) an organohydrogenpolysiloxane having only silicon-bonded hydrogen atoms at both ends of the molecular chain, and the silicon-bonded hydrogen atoms in component (C) are in an amount of 0.1 to 1.20 mol per 1 mol of the total amount of carbon-carbon double bonds in the composition.
8. The electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein The shear storage modulus (G') of the electrode layer composed of the organopolysiloxane cured product obtained by the curing reaction at 110°C is 1.0×10 4 ~1.5×10 6 Within the range of Pa.
9. A laminate having a structure in which two or more layers of organopolysiloxane cured films having different compositions are laminated, and having A structure in which (L2) an electrode layer obtained by a curing reaction of the electrode layer-forming curable organopolysiloxane composition according to any one of claims 1 to 8 is laminated on at least one surface of a cured organopolysiloxane film (L1) as a dielectric layer.
10. The laminate according to claim 9, comprising: (L1) The organic polysiloxane cured film as the dielectric layer is a cured film formed by curing through a hydrosilylation reaction, and (L2) the electrode layer is obtained by a curing reaction of the electrode layer-forming curable organic polysiloxane composition described in any one of claims 1 to 8, wherein the organic polysiloxane cured film as the dielectric layer and the electrode layer are chemically bonded at their interface.
11. A transducer member, comprising the laminate according to claim 9 or 10. 12 . A transducer comprising the laminate according to claim 9 or 10. 13 . An electronic component or a display device comprising the laminate according to claim 9 or 10.
14. The method for producing a laminate according to claim 9 or 10, comprising: Step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film form, thereby obtaining an organopolysiloxane cured film as a dielectric layer; Step II: simultaneously with or after step I, a step of applying the electrode layer-forming curable organopolysiloxane composition according to any one of claims 1 to 8 onto the organopolysiloxane cured film or its precursor in step I to form an electrode layer by a curing reaction thereof. 15 . A method for forming an electrode layer in a transducer member, comprising the method for producing a laminate according to claim 14 .
Citation Information
Patent Citations
JP1977008854B2
Carbasilatrane derivative, its production, adhesion accelerator and hardenable silicone composition
JP1998195085A
Curable organopolysiloxane composition for transducers and applications of such curable silicone composition for transducers
WO2014105959A1
Multilayer body composed of cured organopolysiloxane films, use of same, and method for producing same
WO2022004462A1